Tuberculosis of the Oral Cavity Affecting Alveolus: A Case Report - Bipin Kumar (Case Reports in Dentistry)
We report a first case of tuberculosis of oral cavity affecting the left alveolus from Nepal in a 63-year-old male who came to otorhinolaryngology outpatient department with a complaint of an ulcer in the oral cavity and pain in bilateral ear and throat. An ulcer measuring 1.8 cm in diameter with irregular friable margin and bleeding on touch was found in the left upper alveolar region of the oral cavity. Biopsy from the ulcer margin revealed histological features of necrotizing granulomatous lesion. Stain for acid fast bacilli was positive.